Inhibition of the CXCL9-CXCR3 axis suppresses the progression of experimental apical periodontitis by blocking macrophage migration and activation - Hasegawa, Tatsuya (Sci Rep, 2021)
Apical periodontitis (AP) is an acute or chronic inflammatory disease caused by complex interactions between infected root canal and host immune system. It results in the induction of inflammatory mediators such as chemokines and cytokines leading to periapical tissue destruction. To understand the molecular pathogenesis of AP, we have investigated inflammatory-related genes that regulate AP development. We found here that macrophage-derived CXCL9, which acts through CXCR3, is recruited by progressed AP. The inhibition of CXCL9 by a CXCR3 antagonist reduced the lesion size in a mouse AP model with decreasing IL-1β, IL-6 and TNFα expression. The treatment of peritoneal macrophages with CXCL9 and LPS induced the transmigration and upregulation of osteoclastogenic cytokines such as IL-1β, IL-6 and matrix metalloprotease 2, a marker of activated macrophages. This suggests that the CXCL9-CXCR3 axis plays a crucial role in the development of AP, mediated by the migration and activation of macrophages for periapical tissue destruction. Our data thus show that CXCL9 regulates the functions of macrophages which contribute to AP pathogenesis, and that blocking CXCL9 suppresses AP progression. Knowledge of the principal factors involved in the progression of AP, and the identification of related inflammatory markers, may help to establish new therapeutic strategies.